Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1002/ajp.20709
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of circulating concentrations of gonadotropins and ovarian hormones throughout the menstrual cycle in the bonnet monkey: role of inhibin A in the regulation of follicle‐stimulating hormone secretion

Abstract: In higher primates, increased circulating follicle-stimulating hormone (FSH) levels seen during late menstrual cycle and during menstruation has been suggested to be necessary for initiation of follicular growth, recruitment of follicles and eventually culminating in ovulation of a single follicle. With a view to establish the dynamics of circulating FSH secretion with that of inhibin A (INH A) and progesterone (P(4)) secretions during the menstrual cycle, blood was collected daily from bonnet monkeys beginnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Studies demonstrating the ability of human chorionic gonadotropin (hCG) to prevent the luteal regression and premenstrual decline of serum inhibin levels during the late luteal phase and following GnRH antagonist administration [69] confirmed CL being the source of inhibin during the luteal phase. Studies involving lutectomy in monkeys and other studies in human further confirmed the source of circulating inhibin during the luteal phase in the reproductive cycle [39,40,70]. Subsequent development of sensitive assays and measurement using these assays showed similar pattern of secretion of inhibin A.…”
Section: Pituitary Actions Of Inhibinsmentioning
confidence: 79%
See 3 more Smart Citations
“…Studies demonstrating the ability of human chorionic gonadotropin (hCG) to prevent the luteal regression and premenstrual decline of serum inhibin levels during the late luteal phase and following GnRH antagonist administration [69] confirmed CL being the source of inhibin during the luteal phase. Studies involving lutectomy in monkeys and other studies in human further confirmed the source of circulating inhibin during the luteal phase in the reproductive cycle [39,40,70]. Subsequent development of sensitive assays and measurement using these assays showed similar pattern of secretion of inhibin A.…”
Section: Pituitary Actions Of Inhibinsmentioning
confidence: 79%
“…The primate CL is unique, in that along with progesterone (P 4 ) biosynthesis, it also synthesizes substantial amounts of estradiol (E 2 ) and inhibin A isoform. The fact that CL is the major source of inhibin during the luteal phase was confirmed by the observation of rapid decrease in immunoreactive inhibin levels following lutectomy in cynomolgus monkeys and specific inhibin A levels in bonnet monkeys [39,40]. The secretion of inhibin A in CL appears to be regulated by LH, since inhibition of pituitary LH secretion by treatment with gonadotropin releasing hormone receptor (GnRH-R) antagonist caused a rapid decline in circulating inhibin and inhibin-α subunit mRNA levels [40][41][42][43][44].…”
Section: B Inhibins In Female Gonadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adult female bonnet monkeys ( Macaca radiata ) weighing 3.3-5.1 kg were utilized for the study. The general care and housing of monkeys have been described elsewhere [21]. In this study, one day after occurrence of peak E 2 surge was designated as day 1 of the luteal phase, and CL was collected on designated days of the luteal phase and/or after administration of different treatments (see below).…”
Section: Methodsmentioning
confidence: 99%